Diagnostic accuracy of ultrasonographic features in detecting thyroid cancer in the transition age: a meta-analysis. Issue 3 (14th June 2022) - Cozzolino, Alessia; Filardi, Tiziana; Simonelli, Ilaria; Grani, Giorgio; Virili, Camilla; Stramazzo, Ilaria; Santaguida, Maria Giulia; Locantore, Pietro; Maurici, Massimo; Gianfrilli, Daniele; Isidori, Andrea M; Durante, Cosimo; et al.
Abstract : Context: Significant uncertainty exists about the diagnostic accuracy of ultrasonographic (US) features used to predict the risk of thyroid cancer in the pediatric population. Moreover, there are no specific indications for thyroid nodule evaluation in patients during the transition age. Objective: The meta-analysis aimed to address the following question: which thyroid nodule US features have the highest accuracy in predicting malignancy in the transition age. Methods: We performed a meta-analysis of observational/cohort/diagnostic accuracy studies dealing with thyroid nodule sonography, reporting US features, and using histology as a reference standard for the diagnosis of malignancy and histology or cytology for the diagnosis of benignity in the transition age (mean/median age 12–21 years). Results: The inclusion criteria were met by 14 studies, published between 2005 and 2020, including 1306 thyroid nodules (mean size 17.9 mm) from 1168 subjects. The frequency of thyroid cancer was 36.6%. The US features with the highest diagnostic odds ratio (DOR) for malignancy were the presence of suspicious lymph nodes (DOR: 56.0 (95% CI: 26.0–119.0)), a 'taller than wide' shape of the nodule (6.0 (95% CI: 2.0–16.0)), the presence of microcalcifications (13.0 (95% CI: 6.0–29.0)) and irregular margins (9.0 (95% CI: 5.0–17.0)). Heterogeneity among the studies was substantial. Conclusions: Following the diagnosis of a thyroid nodule in the transition age, a thorough US examination of the neck is warranted. The detection of suspicious lymph nodes and/or thyroid nodules with a 'taller than wide' shape, microcalcifications, and irregular margins is associated with the highest risk of malignancy in the selection of nodules candidates for biopsy.